2021
DOI: 10.21203/rs.3.rs-537337/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial distribution and associated factors of antenatal care utilization in Ethiopia in 2019: Spatial and multilevel analysis

Abstract: Background: Antenatal care utilization key to reduces pregnant women death and preparing women for birth. In Ethiopian antenatal care utilization was still not meet health sector transformation plan. There was also regional variation of antenatal care services in the country. Therefore, current study was aimed to explore spatial distribution and associated factors of antenatal care utilization in Ethiopia based on the nationally representative EMDHS data.Methods: Secondary data analysis was done on 2019 Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
4
1
0
Order By: Relevance
“…Findings show that ANC prevalence varies from one region (or province) to another and decreases from Bujumbura-Mairie(urban area) to the most remote regions and provinces(rural areas). These findings are consistent with findings of two recent studies, all conducted in Ethiopia, which showed a high ANC prevalence in urban areas (Addis Ababa) than rural areas [28, 29]. Regional antenatal care disparities in Burundi, especially when compared to capital of the country (Bujumbura-Mairie), are consistent with findings reported in another recent study [30].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Findings show that ANC prevalence varies from one region (or province) to another and decreases from Bujumbura-Mairie(urban area) to the most remote regions and provinces(rural areas). These findings are consistent with findings of two recent studies, all conducted in Ethiopia, which showed a high ANC prevalence in urban areas (Addis Ababa) than rural areas [28, 29]. Regional antenatal care disparities in Burundi, especially when compared to capital of the country (Bujumbura-Mairie), are consistent with findings reported in another recent study [30].…”
Section: Discussionsupporting
confidence: 92%
“…High predicted prevalence were detected in Muyinga and Kirundo junction, Bururi and Rumonge junction, Bujumbura-Mairie and Bujumbura Rural. These findings are in line with previous study conducted in Ethiopia and Indonesia [28, 37, 38]. In contrast, lower prevalence was observed in several locations of Burundi especially in remote provinces (Ruyigi, Bubanza, Cankuzo, Bubanza and Cibitoke).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the EDHS report, Afar, Somali, and Oromia had the lowest coverage of most RMNCH services [41]. Another study showed that the use of RMNCH services in pastoralist regions of the country, such as Afar and Somali, and SNNPR is extremely low [55]. Ethiopia's pastoral communities occupy 61% of the total landmass and 97% reside in the lowland areas of Afar, Somali, Oromia, Gambella, and SNNPR [56].…”
Section: Discussionmentioning
confidence: 99%